2018
DOI: 10.17576/pengurusan-2018-52-15
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Stock Market’s Dynamic Integration with Asian Stock Markets and World Stock Markets

Abstract: The study examines the relationship and integration of stock markets by using a DCC-GARCH from the period of is chosen because in this period there has been a revocation of foreign ownership restrictions on the Indonesia Stock Exchange. By using this dynamic approach, the relationship, even the integration, of the ever-changing stock markets need to be analyzed with an approach that can accommodate and capture the dynamism of emerging stock markets studied in more detail. Beside DCC-GARCH, several additional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 18 publications
5
19
1
7
Order By: Relevance
“…This is higher than all period and pre-GFC period. This finding also consistent with Robiyanto (2018b). Meanwhile, the principal component (PC) 2 has an eigenvalue of 0.717 with a proportion of 0.079.…”
Section: During the Gfc Period (July 2007 -December 2008)supporting
confidence: 82%
See 1 more Smart Citation
“…This is higher than all period and pre-GFC period. This finding also consistent with Robiyanto (2018b). Meanwhile, the principal component (PC) 2 has an eigenvalue of 0.717 with a proportion of 0.079.…”
Section: During the Gfc Period (July 2007 -December 2008)supporting
confidence: 82%
“…This finding is also supported by the results of Robiyanto (2018b) study which used dynamic methods in predicting capital market integration in ASEAN countries. Robiyanto (2018b) found that capital markets in ASEAN countries tended to have stronger dynamic correlations after the GFC.…”
Section: Asian Stock Markets Integrationmentioning
confidence: 97%
“…In literature related with the stock market and bond market, there is a "flight-to-quality" phenomenon, which explains that investors tend to shift their capital from risky investments like stocks to safer investments like bonds. This opinion is supported by Baur and Lucey (2009), Durand et al (2009), Guler and Ozlale (2005), Robiyanto (2018aRobiyanto ( , 2018bRobiyanto ( , 2018c, Robiyanto et al (2017aRobiyanto et al ( , 2017b. Their research results revealed that during a financial fluctuation period (financial crisis), investors tend to switch from high risk assets (like stocks) to safer assets (bonds).…”
Section: "Flight-to-quality" Phenomenonmentioning
confidence: 88%
“…The following describes the definitions of the operational variables used in this study. Returns on the Indonesian stock market were calculated from the CSPI's returns by applying this following formula (Robiyanto 2018b Return on gold per gram in rupiah (GOLDIDR) was calculated from GOLDIDR which was counted by converting the world gold price per troy ounce in US dollars (GOLD) into rupiah per gram by following the US dollar exchange rate against the rupiah (USDIDR). The calculation was done as follows:…”
Section: Variablesmentioning
confidence: 99%